Peran Posdaya dalam Pengembangan Pendidikan Anak Usia Dini di Kelurahan Bubulak - Nadia Nur Rahmadani; Yannefri Bakhtiar; Amiruddin Saleh (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2020)
Posdaya is one element of a section within a community. One of the fields contained in it i.e. the education. Early childhood education is one of the methods or the way done by the Posdaya to develop their community. Therefore the purpose of this activity is to find out the role of Posdaya in the development of early childhood education in Kampung Batu Hulung, Bubulak Vi, district of Bogor Coal through SUIJI-SLP (Six University Initiative Japan Indonesia – Service Learning Program). Methods used i.e. by means of observation and in-depth interviews to the community. Keywords: community development, early childhood education, posdaya